The Journal of Nursing Measurement Continuity Index Measures in the Acute Care Hospital Setting: An Analytic Review and Tests Using Electronic Health Record Data and Computer Simulation - Yao, Yingwei (J Nurs Meas, 2018)
BACKGROUND AND PURPOSE: Multiple continuity indexes are available, however, their properties are not understood sufficiently for examining the influence of nurse staffing pattern on patient outcomes. We examined continuity measures to understand their properties and potential limitations for measuring nursing care continuity. METHODS: We examined the behavior of continuity indexes as applied to clinical practice data that were collected with the Hands-on Automated Nursing Documentation System and data from computer simulation. RESULTS: Different continuity measures exhibited very different statistical characteristics. Most importantly, many continuity measures contain a length-of-stay dependent term that is uncorrelated with continuity. CONCLUSION: Findings provide a deep understanding of the conceptual foundations and properties of various continuity measures that will help researchers select proper measures and interpret analysis outcomes in their research.